Voltammetric behaviour of mitoxantrone at a DNA-biosensor - Brett, A. M. Oliveira (1998)
The surface of an electrochemical glassy carbon electrode was modified with a layer of double-stranded DNA (dsDNA) or with double-stranded DNA conditioned in single-stranded DNA (ssDNA) and was used to investigate mitoxantrone-DNA interactions. Differential pulse and square wave voltammetry were applied to develop an electroanalytical procedure for the determination of mitoxantrone and evaluate its interaction with dsDNA or ssDNA immobilized on the electrode surface. The results demonstrate that MTX interaction with DNA is not specific to either guanine or adenine bases. The kinetics of the mitoxantrone-DNA interaction is slow and damage to DNA was followed with time.